Dinâmicas culturais e ambientais na praia de Jericoacoara, Jijoca de Jericoacoara, Ceará – Brasil - Viana, Verônica Pontes (2018)
This thesis discusses the long history of the Jericoacoara beach, State of Ceará, Brazil, circumscribed to the National Park of Jericoacoara, located in the Guriú - Doce River interfluve, 287 kilometers from the state’s capital, Fortaleza. The available dates for the area, made by the Carbon 14 method (traditional and AMS), are accommodated in a chronological horizon between 2030 and 1110 years BP (Before the Present). The long stay in periods of contact and post-contact, for which we do not have archaeological dates, was treated from the analysis of historical sources (travel narratives, administrative and cartographic documents), especially related to the first half of the 17 thcentury, when it was made late (compared to other Brazilian captaincies), the colonization of the territory related to the current state of Ceará. In the course of this work, we characterize an environment of coastal occupation, not shell-mounds, from the investigation of the site Jericoacoara I (CNSA 00129 / CE), which we identified as a "site in dune environments", in an imminent destruction process due to the intense wind erosion to which the area is submitted, although points with preserved stratigraphy are still identified. The aforementioned characterization, subsidized by the study of the environmental and previous conditions, occurred with the demonstration of the process of formation and destruction of the archaeological record, influenced by the wind erosion that overlaps the sedimentary matrix that shelters the artefactual arrangements. We have analyzed the specificities of the ceramic collection, the most abundant in the area; of chipped and polished lytic instruments; besides specimens of the malacological remains in which stand out as edible species the gastropod Turbinella Laevigata and the bivalve Anomalocardia flexuosa. The ceramic material has three distinct sets that we called "types", from which we perceive some similarities with certain identified cultural traditions/phases, such as the Papeba phase (Type 1 of Jericoacaora), the Mina (Type 2 of Jericoacoara) and the Tupiguarani (Type 3 of Jericoacoara), this last one, possibly representative of fleeting passages in the Jericoacoara's cove; however, we found significant differences between the types analyzed in this thesis and those already systematized in other parts of Brazilian territory. For this reason, we have focused our efforts on the characterization of the artefactual variability of the complete recorded set, attending to the formal, spatial, relational and frequency aspects that identify the material culture of this coastal interjacent.